#### Answer

Adding like terms results in a like term whose
coefficient is the sum of the coefficients,
and variable factor is equal to the two that are being added.
(please see step-by-step for examples)

#### Work Step by Step

The process of combining like terms is similar to "adding apples":
(two apples)+(three apples)=five apples.
Adding like terms results in a like term whose
coefficient is the sum of the coefficients,
and variable factor is equal to the two that are being added.
Examples:
$5x+2x=(5+2)x=7x$
$32ab-25ab=32ab+(-25ab)=(32-25)ab=7ab$